THE INFLUENCE OF RECIPROCAL TEACHING STRATEGY AND STUDENTS’ LEARNING MOTIVATION ON THE ELEVENTH GRADE STUDENTS’ READING COMPREHENSION ACHIEVEMENT AT BINA JAYA SENIOR HIGH SCHOOL OF PALEMBANG - Nita Ria (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2016)
The research to improve able students’ reading comprehension with used Reciprocal teaching strategy. In this study, the experimental method is used. Bast and Khan (1989:112) states that:An experiment involves the comparison of the effects of a particular treatment with that of different treatment or of no treatment. In a simple conventional experiment, reference is usually made to an experimental group and to a control group.And the variables may have one or more levels. Further, Fraenkel and Wallen (1991:245) say, factorial design extends the number of relationship that may be examined in an experimental. The technique in collecting the data, the researcher uses two techniques: testing and questionnaire. Before the data analysis is done, descriptive statistics analysis of the students pretest and posttest score in experimental and control groups, and the test of normality and homogeneity are done to the students’ pretest and posttest of the two groups and the students’ questionnaire. The researcher uses cluster random sample. The sample to be used is the eleventh grade students Bina Jaya Senior High School of Palembang. Two classes are chosen in which one class become control class and another class to be experimental class. There are 30 students for each group: a) experimental group that is taught reading comprehension using Reciprocal Teaching Strategy, and 30 students would be grouped into a control group.The value of kurtosis of the posttest was -1.029 while the standard error of kurtosis was .833. The difference was -1.862 indicating that the distribution of the posttest score is considered normal. The mean score of the posttest was 62.67. The value of kurtosis of the posttest was 3.112, while the standard error of kurtosis was .833. The difference was 3.945.